Sedimentary DNA insights into Holocene Adélie penguin (Pygoscelis adeliae) populations and ecology in the Ross Sea, Antarctica - Jamie R. Wood; Chengran Zhou; Theresa L. Cole; Morgan Coleman; Dean P. Anderson; Phil O’B. Lyver; Shangjin Tan; Xueyan Xiang; Xinrui Long; Senyu Luo; Miao Lou; John R. Southon; et al. (Nature Communications)
Abstract We report 156 sediment metagenomes from Adélie penguin (Pygoscelis adeliae) colonies dating back 6000 years along the Ross Sea coast, Antarctica, and identify marine and terrestrial eukaryotes, including locally occurring bird and seal species. The data reveal spatiotemporal patterns of Adélie penguin diet, including spatial patterns in consumption of cnidarians, a historically overlooked component of Adélie penguin diets. Relative proportions of Adélie penguin mitochondrial lineages detected at each colony are comparable to those previously reported from bones. Elevated levels of Adélie penguin mitochondrial nucleotide diversity in upper stratigraphic samples of several active colonies are consistent with recent population growth. Moreover, the highest levels of Adélie penguin mitochondrial nucleotide diversity recovered from surface sediment layers are from the two largest colonies, indicating that sedaDNA could provide estimates for the former size of abandoned colonies. SedaDNA also reveals prior occupation of the Cape Hallett Adélie penguin colony site by southern elephant seal (Mirounga leonina), demonstrating how terrestrial sedaDNA can detect faunal turnover events in Antarctica driven by past climate or sea ice conditions. Low rates of cytosine deamination indicate exceptional sedaDNA preservation within the region, suggesting there is high potential for recovering much older sedaDNA records from local Pleistocene terrestrial sediments.